2020
DOI: 10.1016/j.jinf.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as prognosticator in patients with COVID-19

Abstract: Quantifying the importance of the key sites on haemagglutinin in determining the selection advantage of influenza virus: Using A/H3N2 as an example Dear Editor , Authors' contributionsSZ and MHW conceived the study. SZ carried out the analysis, and drafted the first manuscript. SZ and MHW discussed the results. All authors read, revised the manuscript, and gave final approval for publication. Declaration of Competing InterestMHW is a shareholder of Beth Bioinformatics Co., Ltd, and BCYZ is a shareholder of Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
161
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 6 publications
14
161
0
3
Order By: Relevance
“…It is related to a hyperinflammatory status comprising a number of proinflammatory cytokines and chemokines, one of the most predominant being bx;1interleukin 6 (IL-6). 11,12 Given the potential deleterious effect of IL-6 in COVID-19 pneumonia, [13][14][15] we first evaluated the benefit-risk effect of tocilizumab (TCZ), an anti-human IL-6 receptor (IL-6R) monoclonal antibody that inhibits IL-6 signaling by binding soluble IL-6R and membrane IL-6R and is approved for rheumatoid arthritis, juvenile inflammatory arthritis and refractory giant cell arteritis. Tocilizumab is also approved for systemic inflammatory response caused by the massive release of proinflammatory cytokines in response to iatrogenic disease (eg, chimeric antigen receptor T-cell therapies).…”
mentioning
confidence: 99%
“…It is related to a hyperinflammatory status comprising a number of proinflammatory cytokines and chemokines, one of the most predominant being bx;1interleukin 6 (IL-6). 11,12 Given the potential deleterious effect of IL-6 in COVID-19 pneumonia, [13][14][15] we first evaluated the benefit-risk effect of tocilizumab (TCZ), an anti-human IL-6 receptor (IL-6R) monoclonal antibody that inhibits IL-6 signaling by binding soluble IL-6R and membrane IL-6R and is approved for rheumatoid arthritis, juvenile inflammatory arthritis and refractory giant cell arteritis. Tocilizumab is also approved for systemic inflammatory response caused by the massive release of proinflammatory cytokines in response to iatrogenic disease (eg, chimeric antigen receptor T-cell therapies).…”
mentioning
confidence: 99%
“…Yong et al identified the cut-off value of 24.3 pg/ml of IL-6 combining with D-Dimer for early detection of severe cases in a cohort of 43 cases [ 8 ]. Giofoni et al identified a cut-off value of 25 pg/ml of serum IL-6 as an independent risk factor of progression for severe COVID-19 and/or in-hospital mortality in a cohort of 77 patients [ 19 ]. In another cohort in Munich, elevated IL-6 (> 80 pg/ml) was strongly associated with a 22 times higher need for mechanical ventilation compared with patients with lower IL-6 levels in a cohort involving 40 patients, suggesting that high IL-6 level might predict the critical illness [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most investigated cytokines in COVID-19 is IL-6, as it is one of the main mediators of the inflammatory and immune response. In fact, IL-6 levels at hospital admission are considered to have a good prognostic value for severe disease progression and/or in-hospital mortality (Grifoni et al, 2020). IL-6 can be more easily measured in blood than others cytokines and is therefore currently being used to evaluate hyperinflammation and the need for specific anti-inflammatory treatment in hospitalized COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%